The property mining - Gutiérrez Guardia, Carlos Amado (2010)
The origin of the mining property, along the history, has been explain through the basis of two theories. The theory of the accession and the theory of the separation. The first part reffers to the unit of the soil and the subsoil; the second one distinguishes and separates the property of the soil from the subsoil. The theory of the accession considers that the surface (soil) and the deposit (subsoil) are a unit as the mineral deposits are incorporated into the superficial property. The mines belong to the holder of the surface for being an accesory to this one, this argument takes root in the natural Law. Therefore, the mines cant be exploited independently of the soil, faculty reserved only to the owner of the surface who can exploit them freely. The theory of the separation is opposed to the accession for considering to the mining property a different foreign good separated from the superficial property. It thinks that the mines have a different value from the superficial area, because soil and subsoil are two different concepts and each one begins where finishes the other one. This theory has derived in other systems that differs in facts aspects but in the bottom they coincide that the indisputable holder of mining property is the State who can arrange the form of work of the mines for his utilization. In Perú the legislative wil across constitucional and ordinary procedure in mining matter from the first Code of Mining industry of 1900 has postulated the system of the separation, specifically for the systems dominial and regaliano in whose considerations the mines are a property of the Nation and the State is sovereign in his utilization. This one can excercise in direct way realizing buissenes activity and indirectly by means of the system of grants.